High resolution FTIR study of 34S16O2: The bands 2ν1, ν1+ν3,ν1+ν2+ν3−ν2 and ν1+ν2+ν3; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 169 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Bekhtereva E. S. Elena Sergeevna; Gromova O. V. Olga Vasilievna; Buttersack T.; Sydow C.; Bauerecker Z. (S.) H. Zigurd (Sigurd) Hermann (2016, 2016)
Title screen